2011
DOI: 10.1143/jjap.50.066201
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Trench Oxidation in Downstream of Microwave Oxygen Plasma

Abstract: For one application of nonequilibrium oxygen plasma, low-temperature silicon trench oxidation is examined under the conditions of radio frequency bias as well as DC bias applications. The silicon oxidation has a very strong dependence on the substrate bias and is drastically reduced under the condition of no bias. The oxidation depth shows a maximum in a far downstream position from the microwave window. The silicon trench oxidation mapping clearly demonstrates that the maximum depth occurs along the line of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…25,26 However, in these plasma conditions where the substrate is floated in the plasma, the substrate sheath potential determined by the difference (V p À V f ) is positive. The positive ions are, thus, attracted to the substrate to avoid charge-up, 27 it was found that (V p À V f ) is about 20 V at Z 1 and about 10 V at Z 2 . Our findings suggest that not only the negative ions mediate the oxidation of silicon surface, but also the positive ions and eventually the atomic oxygen, especially when the substrate is unbiased.…”
Section: Samples Characterizationmentioning
confidence: 99%
“…25,26 However, in these plasma conditions where the substrate is floated in the plasma, the substrate sheath potential determined by the difference (V p À V f ) is positive. The positive ions are, thus, attracted to the substrate to avoid charge-up, 27 it was found that (V p À V f ) is about 20 V at Z 1 and about 10 V at Z 2 . Our findings suggest that not only the negative ions mediate the oxidation of silicon surface, but also the positive ions and eventually the atomic oxygen, especially when the substrate is unbiased.…”
Section: Samples Characterizationmentioning
confidence: 99%